2017
DOI: 10.1097/aln.0000000000001889
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Acts on Ubiquitination–Proteasome Pathway to Reduce Postsynaptic Density 95 Protein Levels in Young Mice

Abstract: Background Children with multiple exposures to anesthesia and surgery may have an increased risk of developing cognitive impairment. Sevoflurane, a commonly used anesthetic in children, has been reported to decrease levels of postsynaptic density 95 protein. However, the upstream mechanisms and downstream consequences of the sevoflurane-induced reduction in postsynaptic density 95 protein levels remains largely unknown. We therefore set out to assess whether sevoflurane acts on ubiquitination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 60 publications
1
56
0
Order By: Relevance
“…The reduction of synaptic markers has been shown to be associated with decreases in synapse number or synaptic loss. Our results are consistent with the notion that anesthetic-induced reduction in GAP43 and PSD 95 may lead to decreased neuroplasticity and cognitive impairments in developing brain (Wang et al, 2012 ; Zhang et al, 2015 ; Lu et al, 2017 ).…”
Section: Resultssupporting
confidence: 92%
“…The reduction of synaptic markers has been shown to be associated with decreases in synapse number or synaptic loss. Our results are consistent with the notion that anesthetic-induced reduction in GAP43 and PSD 95 may lead to decreased neuroplasticity and cognitive impairments in developing brain (Wang et al, 2012 ; Zhang et al, 2015 ; Lu et al, 2017 ).…”
Section: Resultssupporting
confidence: 92%
“…In particular, synapsin1, vesicular glutamate transporters (VGluT1), PSD95, and Homer1a are classical markers of presynaptic and postsynaptic proteins, which play an important role in synaptic activity [54][55][56][57][58][59]. Previous research has reported that the repeated sevoflurane exposure downregulates synaptic proteins such as postsynaptic protein PSD95 in the hippocampus of developing mice [60,61]. In the present study, we detect the effect of sevoflurane and resveratrol on the expression of these proteins.…”
Section: Resveratrol Restored Synaptic Protein Expression Ex Vivomentioning
confidence: 60%
“…Thus, 25 μg/kg of dexmedetomidine was sufficient to induce neuroprotection. As many studies have shown that the main reason for the changes in learning and memory ability caused by inhaled anesthetics is mainly due to the prominent plasticity of brain neurons such as synaptic density or reticular formation rather than neuronal abnormalities caused by apoptosis or oxidative stress [31,32]. BDNF plays an important role in the regulation of synaptic plasticity, which is the basis of the brain's ability in learning and remembering.…”
Section: Discussionmentioning
confidence: 99%